Long-term fiscal effects of public pension reform in Norway: A generational accounting analysis - Christian Hagist; Bernd Raffelhüschen; Alf Erling Risa; Erling Vårdal (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2011)
Generational Accounts (GAs) measure the fiscal sustainability of the public sector. We ask whether the contributions from the Government Pension Fund and remaining oil and gas wealth in the ground, together with the pension reform taking effect in 2011, are sufficiently large to secure generational balance in Norway. Our results show that the pension reform has a substantial effect, and contributes as much to generational balance as the total petroleum wealth. Neither increased economic growth per se nor increased fertility contribute to improve the GAs. The structural characteristics of higher employment and lower transfer payments typical for cyclical upturns, improve the GAs substantially. Optimistic assumptions regarding these structural characteristics do not remove the need for further reforms to obtain fiscal sustainability of the Norwegian public sector.
Keywords: H50; J10; 330; Generational Accounting; Norway; Fiscal Policy; Intergenerational redistribution